A Meta Analysis on Cardiac Vascular Disease with Obesity - Kumar, Ravi Shankar; Singh, Atinder Pal; Loveleen; Singh, Amrinder (Journal for Research in Applied Sciences and Biotechnology, 2022)
Increasing evidence suggests that inflammatory and immunological factors present in the general population play a role in the pathogenesis of cardiovascular disease in RA. More than that, RA is treated with a wide range of drugs, many of which have the potential to alter cardiovascular function. Non-steroidal anti-inflammatory medicines (NSAIDs) have been linked to an increased risk, whereas some treatments, like methotrexate and TNF inhibitors, have been linked to a reduced risk. Cardiac catheterization is just one of several possible procedures that can be done on the heart. More than a million people in the United States get cardiac catheterization each year. [1] Any time a surgeon makes incisions into a patient, they must be ready for the possibility of complications, whether they arise from the patient or the surgery itself. Fortunately, the prevalence of these issues has decreased considerably in recent years thanks to developments in cardiac catheterization equipment, advances in the experience of the operators, and the introduction of novel methods. The term "cardiac catheterization" can refer to either a right heart or a left heart catheterization, or both. Depending on the patient's condition, interventional cardiologists can do either diagnostic or therapeutic operations. The dangers and difficulties that can arise during a diagnostic cardiac catheterization are briefly discussed in this article.